2013
DOI: 10.1128/jvi.02260-13
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Viral Evolution and Neutralizing Antibody Response after HIV-1 Superinfection

Abstract: e Investigating the incidence and prevalence of HIV-1 superinfection is challenging due to the complex dynamics of two infecting strains. The superinfecting strain can replace the initial strain, be transiently expressed, or persist along with the initial strain in distinct or in recombined forms. Various selective pressures influence these alternative scenarios in different HIV-1 coding regions. We hypothesized that the potency of the neutralizing antibody (NAb) response to autologous viruses would modulate v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…During the follow-up time, 10 individuals became superinfected with HIV-1 within 2 years after primary infection, which is in agreement with previous studies demonstrating that most superinfections occur within the first 2 years of incident infection [5,8]. One of these superinfected individuals (the first superinfected individual in Table 3) has previously been shown to display evidence for a recombination event between original and superinfected viral populations [34]. The univariate results of our study suggest that a higher number of sexual contacts (more than three contacts per month) and specific HLA alleles may play an important role in the risk of HIV-1 superinfection, whereas race/ethnicity, age, higher frequency of condomless anal intercourse, lower CD4 + T-cell count and higher viral load are not significantly associated with increased superinfection risk in this high-risk cohort of MSM.…”
Section: Discussionsupporting
confidence: 87%
“…During the follow-up time, 10 individuals became superinfected with HIV-1 within 2 years after primary infection, which is in agreement with previous studies demonstrating that most superinfections occur within the first 2 years of incident infection [5,8]. One of these superinfected individuals (the first superinfected individual in Table 3) has previously been shown to display evidence for a recombination event between original and superinfected viral populations [34]. The univariate results of our study suggest that a higher number of sexual contacts (more than three contacts per month) and specific HLA alleles may play an important role in the risk of HIV-1 superinfection, whereas race/ethnicity, age, higher frequency of condomless anal intercourse, lower CD4 + T-cell count and higher viral load are not significantly associated with increased superinfection risk in this high-risk cohort of MSM.…”
Section: Discussionsupporting
confidence: 87%
“…These data taken together suggested that potentially protective IgG neutralizing and binding antibodies were lower prior to re-infection in the superinfected group compared to similar time points for the non-superinfected group, representing potential correlates of HIV-1 protection. These data are also consistent with superinfection studies in intrasubtype B superinfected men having sex with men that have shown lower levels of neutralizing antibodies prior to superinfection (4, 5). However, a reduced antibody response was not observed in studies of multi-clade superinfected Kenyan female sex workers (6); although, in this same cohort, a significantly decreased risk of superinfection after the first year of primary infection was consistent with the development of resistance to re-infection (7).…”
Section: Introductionsupporting
confidence: 88%
“…One participant in this study developed substantial NAb breadth and potency after becoming superinfected. Interestingly, this participant's env sequences were the only ones that had evidence of recombination between initial and superinfecting viruses, as we reported previously (19). Three previous studies (8,20,21) reported that superinfected individuals develop broad and potent NAb (bNAb) responses, with some of them becoming elite neutralizers.…”
Section: Discussionsupporting
confidence: 60%